Microstructure and enhanced volume density properties of FeMn78C8.0 alloy prepared via a cleaner microwave sintering approach. (20th July 2020) - Chen, Guo; Li, Kangqiang; Jiang, Qi; Li, Xinpei; Peng, Jinhui; Omran, Mamdouh; Chen, Jin
Abstract: Smelting fine ore into a block with the lower phosphorus content before entering the furnace can achieve cleaner production and value-added efficiency for ferromanganese alloy enterprises, and microwave sintering technology shows bright application prospects in the secondary utilization of waste materials and environmental-friendly preparation of high-performance alloy materials. In this work, FeMn78C8.0 grade bulk alloy with enhanced volume density properties was efficiently prepared via an environmental-friendly microwave sintering approach, using high-carbon ferromanganese powder with low processing efficiency in factories as the raw material. Results indicate that adding certain carbon can prevent the oxidation behavior of Mn and Fe elements during the sintering process, and the qualified FeMn78C8.0 alloy can be obtained by controlling sintering temperature and duration time, with the optimum sintering conditions determined at 1168 °C for 11 min and with the alloy powder of <75 μm accounting for 63%. Meanwhile, some fine pores and cracks on the surface of FeMn78C8.0 alloy are conducive to the densification of the alloy sample and the internal alloying process of the carcass, further to enhance the volume density properties; and influence of the powder of <75 μm on the volume density properties is more profound than that by the powder of 75 μm–150 μm. Additionally, a higher value of volume density of 5.86 g cm −3 is obtained at 1200 °C holding for 10 min, far beyond the traditionally produced alloy by electric furnace with an average value of 5.56 g cm −3 . The work highlights the efficient application of microwave sintering to the secondary utilization of ferromanganese powder and the environmental-friendly preparation of alloy materials.